Digitalisation, Competitive Advantage, Benefits And Challenges Faced - A Study W.R.T. Urban Bengaluru (International Journal of Environmental Sciences, 2024)
Purpose: The major purpose of the present study is to probe whether Bengaluru consumers are impacting on digitalisation through their demographics. Further, the study also conducted to know about measuring competitive advantages through the three impact effects and also the study conducted to know about the benefits of digitalisation to the consumers. Online shopping is becoming very popular in Bengaluru and it is a type of electronic commerce that offers customers to buy goods and services directly from the sellers through internet. Further, the digitalisation revolution also facilitating digital companies to face the competition and to derive competitive advantage.Theoretical framework: The present study extensively reviewed available literature belonging to different theories affecting consumers while purchasing goods online. The study confirms to the existing consumer behaviour models like psycho analytical model mood upliftment, economic model obtaining discounts, offering promotional and Maslow's theory of need hierarchy (Ready to eat) have found most digitally impulsively. The companies also derive the benefit of facing competition through the explained 3 digitally impact affects.Design / Methodology / Approach: The study belongs to the select location of Bengaluru Metropolis, capital city of Karnataka, which is famous for different types of e-commerce consumers and a large consumer base with different culture, religion and education. A questionnaire in addition to secondary data, which was prior to well known was administered to gather the primary data was used. 100 respondents from select areas of Bengaluru constitute the sample for the study and these respondents were contacted, interviewed and necessary data was gathered.Findings: The study found that all the demographics except gender showing significant variation with high degree of relationship. Further, the study reveals about the benefits of digitalisation and these benefits include saves paper consumption and eco-friendly, widened public trust and need to handle heavy cash is eliminated. The benefit of competitive advantage has been measured after considering three electronic effects on cost leadership, differentiation and concentration and found all the variables varying significantly since p-value is lower to the threshold level. The study also revealed about the challenges faced which includes, cyber security and data privacy, high costs and limited financial capabilities and low digital literacy.